Progress feedback in children and adolescents with internalizing and externalizing symptoms in routine care (OPTIE study): study protocol of a randomized parallel-group trial - Christopher Hautmann; Jana Rausch; Nina Geldermann; Felix Oswald; Danny Gehlen; Martin Hellmich; Kerstin Daniela Rosenberger; Christina Samel; Katrin Woitecki; Daniel Walter; Julia Adam; Lydia Dachs; et al. (BMC Psychiatry, 2021)
Abstract Background Progress feedback provides therapists with progress notes on a regular basis through the continuous assessment of participants throughout their treatment (e.g., symptoms, therapeutic alliance). While for adults the evidence base has increased over the years, progress feedback in the therapy of children and adolescents has not been sufficiently investigated. This manuscript describes the trial protocol of the OPTIE study: a randomized trial that tests the efficacy of a progress feedback system in children and adolescents under conditions of routine care. Methods The study is based on a randomized parallel-group trial with two treatment groups (routine, feedback) at an outpatient unit of a university hospital. The target sample size is 439 families consisting of children and adolescents aged 6 to17 years old with internalizing and/or externalizing symptoms. Both the patients and the therapists are independently assigned to the treatment groups by stratified block randomization. In both treatment groups patients receive routine care behavioral therapy for a study-related 12 months; additionally, in the feedback group, a progress feedback system with three components is applied (monitoring, report, and supervision). For three informants (caregiver, child [≥ 11 years], therapist) surveys are conducted every 6 weeks (e.g., symptoms, goals, motivation). For both treatment groups, comparison data is collected at baseline and at six and 12 months after the beginning of the intervention (pre, inter, post), and includes five informants (blinded clinician, therapist, caregiver, child [≥ 11 years], teacher). Discussion The OPTIE study will contribute to the evidence base of progress feedback in children and adolescents and has the potential to uncover treatments’ effects in the small to medium range. Noteworthy features are the inclusion of children younger than 10 years old and the consideration of a blinded clinician rating. Trial registration German Clinical Trials Register (DRKS) DRKS00016737 ( https://www.drks.de/DRKS00016737 ). Registered 17 September, 2019.